2014
DOI: 10.1007/s00592-014-0645-4
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced insulin sensitivity and acute regulation of metabolic genes and signaling pathways after a single electrical or manual acupuncture session in female insulin-resistant rats

Abstract: One acupuncture session with electrical stimulation improves insulin sensitivity and modulates skeletal muscle gene and protein expression more than manual stimulation. Although electrical stimulation is superior to manual in enhancing insulin sensitivity during stimulation, they are equally effective after stimulation indicating that it is activation of sensory afferents rather than muscle contraction per se leading to the observed changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 33 publications
(54 reference statements)
1
27
0
Order By: Relevance
“…In the present study, we decided to give acupuncture 3 times/week because lower treatment frequency (1–2 times/week) did not improve insulin sensitivity in women with PCOS . Comparisons between manual stimulation and electrical stimulation of the needles demonstrate that electroacupuncture improves insulin sensitivity and modulates skeletal muscle gene and protein expression more than manual stimulation of the needles in rats . In the present study, we combined electrical stimulation with manual stimulation of needles which is a common stimulation paradigm in the clinic.…”
Section: Introductionmentioning
confidence: 95%
“…In the present study, we decided to give acupuncture 3 times/week because lower treatment frequency (1–2 times/week) did not improve insulin sensitivity in women with PCOS . Comparisons between manual stimulation and electrical stimulation of the needles demonstrate that electroacupuncture improves insulin sensitivity and modulates skeletal muscle gene and protein expression more than manual stimulation of the needles in rats . In the present study, we combined electrical stimulation with manual stimulation of needles which is a common stimulation paradigm in the clinic.…”
Section: Introductionmentioning
confidence: 95%
“…We previously demonstrated that a single bout of EA in rats is superior to manual stimulation of the needles, but they are equally effective during the poststimulation period, indicating that it is the activation of sensory afferents rather than muscle contractions per se that causes the observed changes (15). Here, we show that the increased glucose uptake in rats is mediated by activation of sympathetic nerves because blocking adrenergic receptors reverses the increased glucose uptake.…”
Section: Discussionmentioning
confidence: 99%
“…The clamp was performed in animals under anesthesia (15). Insulin (Actrapid, Novo Nordisk, Denmark) was continuously infused at 8 mU/kg/min, and glucose was infused to maintain a blood glucose level of 6 mM.…”
Section: Euglycemic-hyperinsulinemic Clampmentioning
confidence: 99%
See 1 more Smart Citation
“…Other findings suggest that electrical acupuncture stimulation affects more functional signaling pathways related to insulin sensitivity, while manual stimulation of acupuncture needles has a greater effect on glucose tolerance [23]. Furthermore, in female insulin-resistant rats both electrical and manual acupuncture stimulation enhances insulin sensitivity via activation of sensory afferents [24]. Our prospective pilot study (ClinicalTrials.gov NCT02026323) [25] of acupuncture affecting the insulin sensitivity in 81 cases of women with PCOS with IR showed that acupuncture has a significant effect on improving the insulin sensitivity in these patients.…”
Section: Introductionmentioning
confidence: 99%